A Meta-Analysis of the Association between Diabetes Mellitus and Traditional Chinese Medicine Constitution. (4th August 2021) - Bai, Fan; Luo, Hui; Wang, Liying; Zhu, Linghui; Guan, Yuanyuan; Zheng, Yanfei; Li, Lingru; Wang, Qi
Abstract : Objective . To explore the distribution of constitution types of diabetes mellitus (DM) in traditional Chinese medicine (TCM) and to provide evidence-based medicine basis for the prevention and treatment of diabetes. Methods . PubMed, Embase, Web of Science, and three Chinese databases were searched to include research literature on the relationship between diabetes and TCM constitution. The single rate study of cross-sectional literature was conducted with RStudio software, and the control meta-analysis of the diabetic and nondiabetic population was performed with Review Manager 5.3 software. Two independent reviewers assessed the methodological quality of the studies' data. The main outcomes included the distribution of constitutional types in the diabetic population and the odds ratio (OR) between the two. Effect sizes are expressed as proportions or ORs with 95% confidence intervals (CI). Results . A total of 28, 781 diabetic cases were included in 87 articles. Yin-deficiency, phlegm-dampness, and qi-deficiency accounted for 18% (95% CI (15%, 20%), P < 0.01 ), 17% (95% CI (15%, 19%), P < 0.01 ), and 13% (95% CI (11%, 15%), P < 0.01 ) of the total diabetic cases. The risk of diabetes in people with yin-deficiency and phlegm-dampness was 3.06 (95% CI (1.38–6.78), P = 0.006 ) and 1.89 (95%CI (1.05–3.42), P = 0.03 ) times higher than that in those with other constitutions, respectively. The distribution of TCM constitution of DM patients varied significantly in different regions and ages. Conclusion . Yin-deficiency and phlegm-dampness are the common constitution types of diabetic people, and they may also be the risk factors of diabetes. Balanced constitution may be a protective factor of diabetes. More high-quality cohort and case-control studies need to be designed to provide more valuable evidence-based basis for assessing the correlation between DM and TCM constitution.